Predictability of cognitive performance based on functional neuroimaging via fNIRS - Şansal, Fırat. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2014., 2014)
In neuropsychology many tasks have been used to determine the cognitive ability and/or flexibility of individuals to have any prior knowledge about the psychological condition or to state the level of neuropsychological disease of a person. This study presents the relations between behavioral performances and neuronal activation within and between two cognitive tasks; Tower of London (TOL) and color-word matching Stroop test which are utilize to obtain cognitive flexibility on decision making, attention and planning. Functional Near Infrared Spectroscopy method is used as functional neuroimaging tool. fNIRS results revealed that activations for both tasks mainly located in both left and right lateral side of prefrontal cortex. Behavioral outcomes such as reaction times of interference effect of stroop task and total planning time of TOL tasks were compared with neuroimaging findings. Right superior lateral prefrontal cortex (RSLPFC) activity during incongruent-neutral interference showed positive correlation with difference of mean response times for correct answered incongruent and congruent trials. In addition we also observed negative correlation with activation of 7-move TOL task and reaction time in left and right lateral prefrontal cortex. At last, it has been presented that subjects have negative brain response(NBR) which is related with good performance (according to results of correlation analysis) during stroop task showed relatively positive brain response (PBR) during TOL task which indicates also good performance, whereas, lateral activation during TOL task is reduced for subjects have PBR in stroop task which can be stated as bad performance.|Keywords : Cognitive Tasks, fNIRS, Prefrontal Cortex, Executive Functions,Stroop Task, Tower of London.
Keywords: Cognitive therapy -- Methods.